E-commerce and Contracts: An Integrated Analysis - Desita, Arini; Mediawati, Noor Fatimah; Fiddinia, Irta (Proceedings of The ICECRS, 2023)
This data article delves into 16,291 scholarly works retrieved from the Lens.org database, focusing on "e-commerce and contracts." Filtering for journal articles and conference proceedings from an initial pool of 28,292 documents, the analysis highlights top institutions, active authors, and prevalent fields of study in online business law. The dataset, publicly available on Zenodo.org (DOI: https://doi.org/10.5281/zenodo.7340357), aids researchers, authors, and readers in comprehensively exploring and comparing scholarly materials in this domain, fostering further studies and insights in global e-commerce law. Highlights : Comprehensive analysis of 16,291 scholarly documents on e-commerce and contracts. Highlighting top institutions, active authors, and prevalent fields of study. Dataset supports global exploration and comparison for e-commerce law research. Keywords: E-commerce, Contracts, Scholarly Works, Data Analysis, Online Business Law